First Light Curve Modelling Of Eclipsing Binary Systems V1264 Cas, V0664 Lac ANDGSC 0199-2035 - Alenazi, M. S.; Elkhateeb, M. M. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Photometric analysis for the newly discovered systems V1264 Cas, V0664 Lac and GSC 0199-2035 were carried out using the most recent version of the Wilson-Devinney binary star modeling code (WD) based on model atmospheres by Kurucz. Accepted models revealed physical parameters use to adopt the spectral type of the components of the studied systems. Locations of the systems on the theoretical mass-luminosity and mass-radius relations revealed good fit for all the systems components except for the secondary components of the systems; V1264 Cas and GSC 0199-2035 where they lie above the TAMS track. Фотометрический анализ недавно обнаруженных систем V1264 Cas, V0664 Lac и GSC 0199-2035 был проведен с использованием самой последней версии кода моделирования двойных звезд Уилсона-Девинни (WD), основанного на моделях атмосфер Куруца. Принятые модели используют выявленные физические параметры для определения спектрального класса компонентов исследуемых систем. Расположение систем по теоретическим соотношениям масса-светимость и масса-радиус выявило хорошее соответствие для всех компонентов систем, кроме второстепенных компонентов систем; V1264 Cas и GSC 0199-2035, где они лежат над последовательностью TAMS.
Keywords: Astrophysics